Nurse-run preanaesthesia assessment clinics: an initiative towards improving the quality of perioperative care at the ambulatory care centre - Neethu Arun; Khalid Mohammed Ahmed Al-Jaham; Saadiya Ahmad Alhebail; Mohammad Jamal Abdallah Hassan; Refa Hanish Bakhit; Johncy Paulose; Marco AE Marcus; Balakrishnan Ramachandran; Marcus D Lance (BMJ Open Quality)
Introduction Nurse-run preanaesthesia assessment is well established in ambulatory surgery. However, in the Middle East the implementation of such a service is new and needed careful preparation. Aim of this audit is to assess the feasibility and the quality of preoperative assessments by the specially trained nurses, patient and nurse satisfaction and overall perioperative quality of recovery.Methods The nurses were selected and trained first in an accredited programme. Then an implementation period of 3 month was used for them to gain experience. Hereafter, we performed a four-step audit on the quality of preassessment, the patient’s satisfaction, the quality of recovery and adverse events if any. Finally, we also monitored the nurse’s satisfaction of their new advanced role.Results The quality of preanaesthesia assessment was high as with 95% compliance to the accepted standards. In the patient satisfaction survey, all 152 patients were either highly satisfied or satisfied with the nurse-run service. The nurses were also highly satisfied and felt that they were either highly or moderately valued. All the patients who were operated at the ambulatory care services were followed up postoperatively by telephone calls which revealed that most of them were highly satisfied. No major or minor adverse events occurred.Conclusion Our specially trained nurses perform preoperative assessments on high standard without adverse events, while patient and staff satisfaction is very high. Future projects will focus on reducing the rate of cancellation of surgeries, investigating the cost-effectiveness of this approach as well as training the specialised nurses for paediatric preoperative anaesthesia assessments. This model of care could induce further nurse-run models of care in the Middle East.